“Market Day” Learning Media in Implementing Contextual Learning in Elementary Schools - Putri Ageng Yoga; Kukuh Andri Aka; Bagus Amirul Mukmin; Intan Mekar Sari (MIMBAR PGSD Undiksha, 2026)
Mathematics learning still tends to be abstract in elementary school so that it makes it difficult for students to understand the concept of arithmetic operations in a meaningful way. This condition shows the need for learning media innovation that is able to associate the material with the student's real-life context. This research aims to analyze the validity, practicality, and effectiveness of the "Market Day" learning media in supporting contextual learning on addition and subtraction of fractions up to 100,000. This research uses a research and analysis approach with the ADDIE model. The research subjects consist of students in class V and VI who are involved in field trials, as well as teachers as media users. Data was collected through student and teacher response questionnaires, as well as study results tests. Data analysis is carried out descriptively and inferentially to test the differences in learning outcomes between groups. Research results show that "Market Day" media meets valid, practical, and effective criteria in increasing student learning outcomes. This media is able to encourage the active involvement of students through contextual learning activities so that it helps students understand mathematical concepts more concretely. This finding indicates that the use of real activity-based learning media can be an alternative in improving the quality of mathematics learning in elementary schools. The development of similar media with more diverse contexts is recommended to expand the implementation of meaningful learning.